FEATURES OF THE TOK SEN MASSAGE TECHNIQUE AS ONE OF THE METHODS OF SHOCK-VIBRATION MASSAGE - Chopovskyi, D. P. (Rehabilitation and Recreation, 2023)
Objective is studying and analyzing the features of the Tok Sen massage technique as one of the methods of shock-vibration massage. To achieve the objectives, a theoretical analysis was conducted, which included generalization, synthesis, comparison and analysis of the available research results in modern scientific and methodological literature. Results. Based on the results of observations and a review of scientific and methodological literature, Tok Sen massage, also known as Thai hammer massage, originates in Northern Thailand, particularly in the Lanna region, and has been recognized for its unique and scientifically proven effects on the body and mind. This massage technique has been around for more than 4000 years (according to unofficial information), and there is documented evidence of its use in Thailand for 2500 years. Tok Sen was originally developed by the Lanna people as a means of healing and maintaining the well-being of their communities. There are various explanations for the origin of this style of massage. The article discusses percussion-vibration massage techniques and their characteristics. The Tok Sen massage technique is investigated, its features and unique characteristics are studied. In addition, the article conducts a comparative analysis of the impact of shock and vibration methods on physiological processes in the human body. The article examines in detail the aspects of the Tok Sen massage, its physiological and psychological effects on the body. Attention is drawn to the importance of proper performance of the Tok Sen massage technique. The article discusses the indications and contraindications for this type of massage, which helps professionals and patients to take them into account when deciding on a massage procedure. This type of massage promotes relaxation and at the same time energizes from the depths of the soul. The constant rhythmic sound of strokes and deep vibrations lead to a state of meditation and help clear the mind of any distractions. Conclusions. The analysis of the results of scientific and methodological literature showed that the peculiarities of the Tok Sen massage technique as one of the methods of shock-vibration massage is that this type of massage is an important component of modern rehabilitation. This technique, based on the principles of shock vibration, allows for significant improvements in the health of patients with various conditions and diseases. As the demand for evidence-based, holistic wellness practices grows, Tok Sen massage is becoming a powerful tool for promoting physical and emotional well-being. Its ancient wisdom combined with a modern scientific base position it as a promising pathway for deep healing.